Evaluation of Productivity and Financial Feasibility of Broiler Chicken Farming Business Models: Cage and Postal Systems - Wijoyo, Iman Aji; Aribowo, Lely Puspitarini; Kristanti, Novita Dewi (Journal of Agriprecision & Social Impact, 2024)
The growth of the human population and increased purchasing power drive greater demand for broiler meat, posing challenges for farmers to enhance their productivity and business efficiency. The development of closed-house cages offers a solution to improve production efficiency. This study compares the productivity and financial analysis between the cage and postal models. Utilizing a quantitative descriptive method, the research was conducted over a single rearing period in cages and postal setups at PT Dinamika Megatama Citra (DMC) without any specific treatment. Research parameters encompassed body weight gain, mortality, FCR, harvest weight, and Performance Index. Financial analysis was conducted using indicators such as the R/C ratio, B/C ratio, Break-Even Point (BEP), and Return on Investment (ROI). Results indicate that in cage conditions, mortality stood at 4.07%, FCR at 1.718, average weight at 2.2 kg, and Performance Index at 287.5. Meanwhile, postal cages exhibited higher mortality at 8.79%, FCR at 1.732, average weight at 2.3 kg, and Performance Index at 285.6. In financial analysis, cage systems had a BEP price of Rp 19,726/kg with a unit BEP of 40,616 kg, an R/C ratio of 1.039, a B/C ratio of 0.039, and an ROI of 3.92%. Conversely, postal cages had a BEP price of Rp 19,507/kg with a unit BEP of 39,924 kg, an R/C ratio of 1.05, a B/C ratio of 0.05, and an ROI of 5.09%.